Strategi Pengambilan Keputusan melalui Komunikasi Efektif pada Organisasi Publik: Penelitian - Budi Priyono; Muhammad Rizki; Suparno; Saparuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines the role of communication in strategic decision-making in public organizations. In a complex and dynamic environment, stakeholders are struggling with challenges in formulating optimal decisions. Effective communication is key to strengthening transparency, building trust, and increasing participation from various stakeholders. With a literature review approach, this study identifies the best strategies in communication management that support more informative and responsive decision-making to environmental changes. The results of the study indicate that two-way symmetrical communication, information transparency, and strategic crisis management contribute to increasing the efficiency and accuracy of decisions taken. Thus, this study provides insight into the importance of communication strategies in building solid relationships between public organizations and their stakeholders, and how this affects the organization's success in achieving its expected goals.